Determination of Chemical and Microbiological Quality in Commercial Tahini Halva Samples - Zeynep Kilci; Ramazan Ulku Çetin (Turkish Journal of Agriculture: Food Science and Technology)
40 samples of tahini halva from 5 different firms, in 4 distinct varieties—plain, hazelnut, carob, and vanilla—were gathered for this study from producers in the provinces of Balikesir and Bursa as well as from commercial markets. Samples were taken from two different lot numbers for each company. As a result of the analyzes made on the tahini halva samples, it was determined that the total amount of sesame oil varied between 24.67-38.87%, the total amount of tahini ranged between 59.34-69.7%, the total moisture amount was between 0.1-0.9%, the total ash amount was 0.089-3.16%, and the total salt amount was between 0.001-0.024%; as a result of microbiological cultivations in which the presence of yeast and mold were analyzed, an average of 10 cfu/g in plain tahini halva samples, an average of 90 cfu/g in hazelnut tahini halva samples, an average of 45 cfu/g in carob tahini halva samples, and an average of 25 cfu/g in vanilla tahini halva samples were determined. All samples of tahini halva were found to be free of contamination with Salmonella spp., Staphylococcus aureus or Escherichia coli. When all of these findings were taken into consideration, it was found that one of the sampled firms did not produce in accordance with the Turkish Food Codex Communique on Tahini Halva (2015/28) in terms of total sesame oil (%) and ash content (%) of two companies. Combined, the findings of the chemical and microbiological analyses indicate that 85% of the samples were prepared in line with the TFC.